Global thoughts, local designs : INTERACT 2017 IFIP TC 13 Workshops, Mumbai, India, September 25-27, 2017, revised selected papers /: INTERACT 2017 IFIP TC 13 Workshops, Mumbai, India, September 25-27, 2017, revised selected papers. (2018) - Unknown
No abstract available